2016
DOI: 10.4172/2155-6148.1000612
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Prophylactic Antibiotic Administration in Elective Surgical Patients at Jimma University Teaching Hospital: South West Ethiopia

Abstract: Study objective: To evaluate the timing of prophylactic antibiotic administration in elective surgical patients, and anesthetists' opinion regarding this issue.Design: Prospective, facility based cross-sectional study was employed. Setting: Jimma university teaching hospital (JUTH)Patient: Elective surgical patients and anesthesia professional of the hospital.Measurement: Data were collected prospectively from all elective surgical patients (except emergency, obstetric cases) and interred in predesigned forms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 23 publications
5
10
0
Order By: Relevance
“…This research finding indicated that surgical antibiotics commonly practiced in NRH were neither part of the STG of the country nor the primary choice of the international guidelines. Analogous reports were noted in similar studies conducted in different areas of the country [ 7 , 10 ]. Therefore, what one should be skeptical to our country context is that some common custom on broad-spectrum antibiotic use has been held and communicated across (probably) all hospitals of the country that should be further investigated and intervened as soon as possible.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…This research finding indicated that surgical antibiotics commonly practiced in NRH were neither part of the STG of the country nor the primary choice of the international guidelines. Analogous reports were noted in similar studies conducted in different areas of the country [ 7 , 10 ]. Therefore, what one should be skeptical to our country context is that some common custom on broad-spectrum antibiotic use has been held and communicated across (probably) all hospitals of the country that should be further investigated and intervened as soon as possible.…”
Section: Discussionsupporting
confidence: 87%
“…Although the guidelines promote to end prophylactic administration within 24 hours [ 4 , 5 ], 44.4% of the administrations continued for up to five days. Comparable results were reported from a study in Iran (46%) [ 13 ], and in southwestern Ethiopia (50.7%) [ 10 ]. To be specific, in this study only less than a quarter (20.9%) of the patients’ discontinued surgical antibiotics within a day.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations